Advances and novel developments in drug hypersensitivity diagnosis. Issue 12 (9th October 2020) - Ariza, Adriana; Mayorga, Cristobalina; Bogas, Gador; Barrionuevo, Esther; Torres, Maria J.; Doña, Inmaculada; Fernandez, Tahia D.
Abstract: A correct diagnosis of drug hypersensitivity reactions (DHRs) is very important for both the patient and health system. However, DHRs diagnosis is complex, time consuming, requires trained personnel, is not standardized for many drugs, involves procedures not exempt of risk, and in most cases lacks standardized in vivo and in vitro tests. Thus, there is an urgent need for improving the different approaches to diagnose patients with suspected DHRs. In this review, we have analyzed the advances performed in immediate and nonimmediate DHRs diagnosis during the last two years and obtained several conclusions: the significant heterogeneity in current practice among centers illustrates the need to re‐evaluate, update, and standardize in vivo tests and protocols for the diagnosis and management of patients with suspected drug allergy. Regarding in vitro tests, the latest studies have focused on increasing their sensitivity or on establishing the sensitivity and specificity for the tests performed with new drugs. There seems to be a consensus about combining in vivo and in vitro tests as the best way to increase the diagnostic accuracy.